Super-resolved insights into human immunodeficiency virus biology - Hanne, Janina; Zila, Vojtech; Müller, Barbara; Kräusslich, Hans-Georg (FEBS letters, 2016)
The recent development of fluorescence microscopy approaches overcoming the diffraction limit of light microscopy opened possibilities for studying small-scale cellular processes. The spatial resolution achieved by these novel techniques, together with the possibility to perform live-cell and multicolor imaging, make them ideally suited for visualization of native viruses and subviral structures within the complex environment of a host cell or organ, thus providing fundamentally new possibilities for investigating virus-cell interactions. Here, we review the use of super-resolution microscopy approaches to study virus-cell interactions, and discuss recent insights into human immunodeficiency virus biology obtained by exploiting these novel techniques.